Transcranial Direct-Current Stimulation in Subacute Aphasia: A Randomized Controlled Trial. Issue 4 (13th March 2023) - Stockbridge, Melissa D.; Elm, Jordan; Breining, Bonnie L.; Tippett, Donna C.; Sebastian, Rajani; Cassarly, Christy; Teklehaimanot, Abeba; Spell, Leigh Ann; Sheppard, Shannon M.; Vitti, Emilia; Ruch, Kristina; Goldberg, Emily B.; et al.
Abstract : Background: Transcranial direct-current stimulation (tDCS) is a promising adjunct to therapy for chronic aphasia. Methods: This single-center, randomized, double-blind, sham-controlled efficacy trial tested the hypothesis that anodal tDCS augments language therapy in subacute aphasia. Secondarily, we compared the effect of tDCS on discourse measures and quality of life and compared the effects on naming to previous findings in chronic stroke. Right-handed English speakers with aphasia <3 months after left hemisphere ischemic stroke were included, unless they had prior neurological or psychiatric disease or injury or were taking certain medications (34 excluded; final sample, 58). Participants were randomized 1:1, controlling for age, aphasia type, and severity, to receive 20 minutes of tDCS (1 mA) or sham-tDCS in addition to fifteen 45-minute sessions of naming treatment (plus standard care). The primary outcome variable was change in naming accuracy of untrained pictures pretreatment to 1-week posttreatment. Results: Baseline characteristics were similar between the tDCS (N=30) and sham (N=28) groups: patients were 65 years old, 53% male, and 2 months from stroke onset on average. In intent-to-treat analysis, the adjusted mean change from baseline to 1-week posttreatment in picture naming was 22.3 (95% CI, 13.5–31.2) for tDCS and 18.5 (9.6–27.4) for sham and was not significantly different. Content and efficiency of picture description improved more with tDCS than sham. Groups did not differ in quality of life improvement. No patients were withdrawn due to adverse events. Conclusions: tDCS did not improve recovery of picture naming but did improve recovery of discourse. Discourse skills are critical to participation. Future research should examine tDCS in a larger sample with richer functional outcomes. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02674490.